Vestuario ergonómico para salsa vieja guardia - Diaz Echeverry, Laura Camila (Universidad de San Buenaventura - Cali, 2017)
The salsa was born in Cuba and was coming through seaports, in the case of the city of Cali the port of Buenaventura. These rhythms were carried grills and nightclubs, where people felt quickly identified by their joy. This allowed popularizing the genre outside, giving way to what we know as the old guard. However, despite the "Old Guard" who was allowed to expand and become known as "The capital of salsa" they have lost much importance, causing much of the history and tradition is lost. Therefore it is appropriate to vindicate this style and again highlight their participation to continue enduring history. To achieve this, and as a contribution from the field of costume design is important to evaluate the apparel worn by an exploratory research, as this has lagged behind in terms of development and innovation, because it is relevant generate ergonomic changes will allow the dancer old Guard not only stand out for its particular style, discipline and tradition but can also perform more efficiently and favorably for your image.